KOMPETENSI TUTOR KEAKSARAAN FUNGSIONAL DALAM PENGELOLAAN PEMBELAJARAN DI KECAMATAN WARA UTARA KOTA PALOPO PROVINSI SULAWESI SELATAN - Akram Akram (JIV-Jurnal Ilmiah Visi, 2006)
In nonformal education, tutors are to assist learners to learn as well as to motivate them. To make these tutors be able to improve their competencies, they should get appropriate/relevant trainings. This article reports a researchs on tutors competency in conducting instruction for functional literacy program in Wara Utara . Research findings show tutor are still lack of competencies in assisting and motivating learners in an instructional situation. Itâ€™s recommended that they should be trained on learning motivation.